Significant trends and structural shifts in rainfall patterns in Nigeria - Obot, Nsikan Ime (Acta hydrotechnica, 2024)
Rainfall, with its varying timescales, impacts weather patterns, living conditions, and the environment. This study aims to evaluate trends and structural shifts in monthly rainfall across 24 locations in Nigeria spanning 51 years (1960-2010). Utilizing the Mann–Kendall test statistic (MK) for trend identification and the cumulative sum method for detecting changes in structure, cyclic patterns, and random components within distributions, the analysis incorporated descriptive statistics, including the coefficient of variation, skewness, kurtosis, and the Jarque–Bera test with associated p-values. Descriptive statistics can behave unusually where abnormal rainfall patterns are common. Despite the nonparametric nature of MK, it occasionally yielded varying values and dissimilar trends between total annual rainfall and total seasonal rainfall, as well as between average annual rainfall and average seasonal rainfall, attributed to high variability. Consequently, a statistically significant trend in total rainfall amounts might not correspond to the trend in mean rainfall amounts. Notably, statistically significant trends may sometimes be accompanied by similar significant structural shifts at every location. However, such trends and shifts are generally more frequent in the northern arid regions, specifically between 9.14°N and 12.53°N. For instance, a statistically significant change in total annual rainfall of 11.15 mm/year was observed in Kano (12.03°N), accompanied by an increasing structural shift around the 40th year of analysis. Conversely, a total annual rainfall significant trend of -3.01 mm/year occurred at Jos (9.52°N), though it was not among the 9 locations with significant structural shifts. Analysis of this nature helps in tackling water-related issues and understanding atmospheric phenomena.
Keywords: analiza kumulativne vsote; arid regions; cumulative sum analysis; hidrologija; hydrology; Mann-Kendall test statistic; Mann–Kendallov test; pomembni trendi; rainfall trends; significant trends; sušne regije; trendi padavin